STUDI PARAMTERIK PERKERASAN JALAN BETON SISTEM PELAT TERPAKU PADA TANAH DASAR LUNAK - Puri, Anas (Proceedings ACES (Annual Civil Engineering Seminar), 2015)
Theapplications of chiken foot foundation (sistem cakar ayam) are shown successfully on runway, taxi way, and apron of airport and gave services more than 30 years. This system is alsoshown the satisfy performance for high way construction. One of developing of this systemwas changing the concrete cylindrical foundation by galvanized cylindrical steel and it isnamed modified chiken foot foundation (CAM). Hardiyatmo (2008) proposed Nailed-slabSystem for more practical application by changing the cylindrical foundation by concrete pilefoundation. Based on model tests and analysis, the Nailed-slab is promising for application.This research is aimed to learn the behavior of Nailed-slab by conducting parametric study.This study was using the full scale test results of chiken foot foundation in Waru, East Java.Results show that the performance of Nailed-slab system (4 × 4 piles and 5 × 5 piles)withsimilar slab width with CAM was better than CAM performance. Slab deflections of Nailedslabtend to be lower than CAM. Similar behaviorswere for moment of slab. Additional of pilelength and decreasing the pile spacing can increase the performance which indicated bydecreasing the deflections.Keywords: chiken foot foundation, Nailed-slab system, soft soils, rigid pavement